2015
DOI: 10.1111/iwj.12522
|View full text |Cite
|
Sign up to set email alerts
|

A treatment algorithm to identify therapeutic approaches for leg ulcers in patients with sickle cell disease

Abstract: Sickle cell leg ulcers (SCLUs) are a common complication of sickle cell disease (SCD). Patients who develop ulcers appear to have a more severe haemolysis-associated vasculopathy than individuals who do not develop them, and manifest other complications such as priapism and pulmonary hypertension. SCLUs are slow to heal and often recur, affecting both the emotional and physical well-being of patients. Here we summarise what is known about the pathophysiology of SCLUs, describe available treatment options and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
67
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(70 citation statements)
references
References 72 publications
0
67
0
3
Order By: Relevance
“…1,2,8 The use of a triple antibiotic cream has been advocated for the treatment of ulcers in patients with SCD after a prospective trial showed a statistically significant decrease in ulcer size. 19 The study population, however, had only 15 patients. 19 A review by Cochrane in 2014 cited a clinical trial using an arginine-glycine-aspartic acid peptide matrix on sickle cell leg ulcers as the only trial achieving noticeable benefit after treatment, with statistically significant decrease in sickle cell leg ulcer size.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…1,2,8 The use of a triple antibiotic cream has been advocated for the treatment of ulcers in patients with SCD after a prospective trial showed a statistically significant decrease in ulcer size. 19 The study population, however, had only 15 patients. 19 A review by Cochrane in 2014 cited a clinical trial using an arginine-glycine-aspartic acid peptide matrix on sickle cell leg ulcers as the only trial achieving noticeable benefit after treatment, with statistically significant decrease in sickle cell leg ulcer size.…”
mentioning
confidence: 99%
“…19 The study population, however, had only 15 patients. 19 A review by Cochrane in 2014 cited a clinical trial using an arginine-glycine-aspartic acid peptide matrix on sickle cell leg ulcers as the only trial achieving noticeable benefit after treatment, with statistically significant decrease in sickle cell leg ulcer size. The Cochrane Group, however, also stated that the study carries a risk of bias and recommends further studies.…”
mentioning
confidence: 99%
See 3 more Smart Citations